The Golden Mare, the Firebird, and the Magic Ring - Sanderson, Ruth (Boston : Little, Brown, 2001)
A young huntsman is helped by a golden mare when he tries to perform the seemingly impossible feats commanded by the Tsar.
"Based on elements from a number of traditional Russian fairy tales, including The Firebird, the Horse of Power and Vasilissa ... [et al]"--T.p. verso.
Keywords: Folklore -- Russia